Enzyme characteristics of extremely halophilic archaeal community in Tuzkoy Salt Mine, Turkey - (:unkn) unknown (SPRINGER, 2004)
Tuzkoy is a large and unpolluted salt mine in Central Anatolia, Turkey. High quality salt in this mine may be supplied to the table salt market after a simple process instead of complicated refining. However, the extremely halophilic microbial content of the salt has not yet been investigated which may result in detrimental effects in industrial processes such the food and leather industries, if unprocessed salt is directly used. Therefore, to identify and characterize the microbial contaminants in Tuzkoy salt, chemical and microbial analyses were conducted on salt crystal samples collected from three different locations of the mine. Generally 10(5)-10(6) colony forming units of extremely halophilic microorganisms were detected per gram of salt samples. Twelve colonies were selected randomly for further characterization. Phenotypic characterization, lipid analysis, antibiotic susceptibility tests and positive PCR amplification results with Archaea-specific primers confirmed that all strains were halophilic Archaea belong to family Halobacteriaceae. According to denaturing gradient gel electrophoresis (DGGE) results, 10 comparatively different strains were selected for DNA sequencing. DNA sequences and phylogenetic analyses revealed that the isolated strains were mainly species of the genera Halobacterium, Haloarcula, Natrinema and Halorubrum. In addition enzymatic activity tests were also conducted to evaluate the salt quality for industrial applications. Results of gelatinase, caseinase, amylase, cellulase and lipase activity tests revealed that the isolated strains produced hydrolytic enzymes, which could cause deterioration in salt-treated food and hide. It may be pointed out that cellulase activity in halophilic Archaea has not been reported previously. Moreover, beta-galactosidase activity has been reported in some Haloferax and Halorubrum species but not in the genus Halobacterium.
Keywords: enzyme activity; extremely halophilic Archaea; Tuzkoy salt mine; BETA-GALACTOSIDASE; BACTERIA; GENE; DIVERSITY; IDENTIFICATION; PURIFICATION; ALIGNMENT; QUALITY; PONDS; GRAIN